Gamma Knife Treatment of Brainstem Metastases - Peterson, Halloran E. (MDPI, 2014)
The management of brainstem metastases is challenging. Surgical treatment is usually not an option, and chemotherapy is of limited utility. Stereotactic radiosurgery has emerged as a promising palliative treatment modality in these cases. The goal of this study is to assess our single institution experience treating brainstem metastases with Gamma Knife radiosurgery (GKRS). This retrospective chart review studied 41 patients with brainstem metastases treated with GKRS. The most common primary tumors were lung, breast, renal cell carcinoma, and melanoma. Median age at initial treatment was 59 years. Nineteen (46%) of the patients received whole brain radiation therapy (WBRT) prior to or concurrent with GKRS treatment. Thirty (73%) of the patients had a single brainstem metastasis. The average GKRS dose was 17 Gy. Post-GKRS overall survival at six months was 42%, at 12 months was 22%, and at 24 months was 13%. Local tumor control was achieved in 91% of patients, and there was one patient who had a fatal brain hemorrhage after treatment. Karnofsky performance score (KPS) >80 and the absence of prior WBRT were predictors for improved survival on multivariate analysis (HR 0.60 (p = 0.02), and HR 0.28 (p = 0.02), respectively). GKRS was an effective treatment for brainstem metastases, with excellent local tumor control.